Thermoeconomic indicators ofair conditioning in a river ship to change the configuration of their thermal insulation (2014)
This work has as object of study the energy of a river ship air conditioning system performance, using fiberglass, polyurethane or rockwool as insulation. Thermoeconomics Indicators based on second law of thermodynamics which take into account the quality of the energy and the cost of the exergy were used for research. It was observed that: (i) by increasing the thickness of the insulation the irreversibilities decreased, (ii) increases in the destroyed exergy increased generation of cooling load costs and (iii) costs per unit of exergy of heat load and area for the generation of cooling load and for investment in exergetic insulation, were minors for polyurethane. Copyright © 2014 by ASME.